Photochemical Analysis of Moringa and Effect of Extract on Inhibition of Aspergillum Niger Development - Yousif Ahmaed Yousif, Hala; M.Abderahim, Awad; A. Idris, Fadlelmoula (Gezira Journal of Engineering and Applied Sciences; مجلد 15 عدد 1 (2020), 2021)
The present study investigated the photochemical and activities of the Moringa Rotifera lam plant extracts against the tested microorganisms (Fungi). The mycelia growth method was used for fungi. (Aspergillum Niger), the seeds, pods, leaves, and stem extracts gave 1.3, 3.0, 3.0 and 6.0 mm diameter, respectively. The seed extracts were most effective against Aspergillum Niger; they gave only 0.1 g dry weight and 3.99 g fresh weight. On the other hand, the stem, leaves and pod extracts were less effective, giving 0.60 g, 0.65g and 0.80g dry weights at the higher concentration (100%), respectively. The chemical analysis showed that the Moringa plant extracts contained flavonoids, tannins, saponins, alkaloids and steroids. From the results, it could be concluded that the Moringa plants' extracts were highly effective against the mycelial growth of fungi (radial growth and weights). The analysis of the active components of the extracts needs to be verified in further studies.